TRAINING ON POETRY WRITING WITH ACROSSTIC TECHNIQUES IN STUDENTS OF CLASS XI SMA METHODIST IV MEDAN - Juni Agus Simaremare; Emelda Thesalonika (Universitas Muhammadiyah Mataram, 2022)
Abstrak: Pengabdian kepada Masyarakat (PkM) ini dilaksanakan pada siswa kelas XI SMA Methodist IV Medan. Tujuan pelaksanaan PkM ini adalah (1) untuk meningkatkan pemahaman dan pengetahuan siswa mengenai prosedur penulisan puisi dengan teknik akrostik; (2) Meningkatkan kreativitas menulis siswa khususnya menulis puisi dengan teknik akrostik. Subjek dalam kegiatan PkM ini ialah siswa-siswi kelas XI SMA Methodist IV Medan yang berjumlah 30 orang. Metode yang digunakan dalam pelatihan ini adalah metode demonstrasi dan metode ceramah. Dalam menjelaskan materi berupa hakikat puisi akrostik dan mekanisme penulisan puisi dengan teknik akrostik digunakan metode ceramah. Dalam praktik menulis puisi dengan teknik akrostik digunakan metode demonstrasi. Kegiatan pelatihan ini dapat terlaksana dengan baik tidak terlepas dari dukungan beberapa unsur yaitu LPPM sebagai lembaga penyedia dana kegiatan pelatihan, kepala sekolah, wakil kepada sekolah, serta para guru sebagai mitra yang memfasilitasi pelaksanaan pelatihan, serta para siswa kelas XI SMA Methodist IV yang sangat antusias mengikuti pelatihan. Hasil dari pelatihan ini adalah siswa secara keseluruhan mampu menulis puisi dengan teknik akrostik. Hasil ini dapat dibuktikan dari nilai rata-rata 79 dengan jumlah skor 2364 dan hasil tersebut termasuk dalam kategori baik.Abstract: This Community Service (PkM) was carried out on class XI students of SMA Methodist IV Medan. The objectives of this PkM implementation are (1) to increase students' understanding and knowledge of the procedures for writing poetry using acrostic techniques; (2) Improving students' writing creativity, especially writing poetry with acrostic techniques. The subjects in this PkM activity were students of class XI SMA Methodist IV Medan, totaling 30 people. The method used in this training is the demonstration method and the lecture method. In explaining the material in the form of the nature of acrostic poetry and the mechanism of writing poetry with acrostic techniques, the lecture method is used. In the practice of writing poetry with acrostic techniques, demonstration methods are used. This training activity can be carried out properly and cannot be separated from the support of several elements, namely LPPM as an institution that provides funding for training activities, school principals, representatives to schools, and teachers as partners who facilitate the implementation of the training, as well as students of class XI SMA Methodist IV who are very enthusiastic. attend training. The result of this training is that overall students are able to write poetry with acrostic techniques. This result can be proven from the average value of 79 with a total score of 2364 and these results are included in the good category.